Prevalence and risk factors for Taenia solium cysticercosis in school-aged children: A school based study in western Sichuan, People's Republic of China. - John J Openshaw; Alexis Medina; Stephen A Felt; Tiaoying Li; Zhou Huan; Scott Rozelle; Stephen P Luby (PLoS Neglected Tropical Diseases, 2018)
Taenia solium cysticercosis affects millions of impoverished people worldwide and can cause neurocysticercosis, an infection of the central nervous system which is potentially fatal. Children may represent an especially vulnerable population to neurocysticercosis, due to the risk of cognitive impairment during formative school years. While previous epidemiologic studies have suggested high prevalence in rural China, the prevalence in children as well as risk factors and impact of disease in low-resource areas remain poorly characterized.Utilizing school based sampling, we conducted a cross-sectional study, administering a questionnaire and collecting blood for T. solium cysticercosis antibodies in 2867 fifth and sixth grade students across 27 schools in west Sichuan. We used mixed-effects logistic regression models controlling for school-level clustering to study associations between risk factors and to characterize factors influencing the administration of deworming medication. Overall prevalence of cysticercosis antibodies was 6%, but prevalence was significantly higher in three schools which all had prevalences of 15% or higher. Students from households owning pigs (adjusted odds ratio [OR] 1.81, 95% CI 1.08-3.03), from households reporting feeding their pigs human feces (adjusted OR 1.49, 95% CI 1.03-2.16), and self-reporting worms in their feces (adjusted OR 1.85, 95% CI 1.18-2.91) were more likely to have cysticercosis IgG antibodies. Students attending high prevalence schools were more likely to come from households allowing pigs to freely forage for food (OR 2.26, 95% CI 1.72-2.98) and lacking a toilet (OR 1.84, 95% CI 1.38-2.46). Children who were boarding at school were less likely to have received treatment for gastrointestinal worms (adjusted OR 0.58, 95% CI 0.42-0.80).Our study indicates high prevalences of cysticercosis antibodies in young school aged children in rural China. While further studies to assess potential for school-based transmission are needed, school-based disease control may be an important intervention to ensure the health of vulnerable pediatric populations in T. solium endemic areas.